A atividade turística e sua territorialidade no espaço rural da AMUSEP, norte do Paraná - Azarias, Franciely Fernandes (2011)
The forms of organization in rural pluriactive refer to social situations in which agriculture or do not necessarily need to be involved, the rural tourism is a typical example. In this activity, the individuals belonging to a family of farmers start to engage in productive economic activities to supplement farm income, and in many cases what was at first turns out to be in addition to base rent that will economically support the property. In this study, we attempted to analyze the organization pluriactivity, taking as reference the performance area and the occurrence of AMUSEP characterized as rural tourism in that area. The methodology, the developments are quantified endowed some structure to receive tourists, interviewed the owners and qualified as their social relations. Photographic material helps to illustrate instances selected, thus allowing the visualization of the structure of attraction and provide services to visitors.